2021
DOI: 10.1038/s41380-020-01001-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin receptor activation rescues cognitive and synaptic abnormalities caused by hemizygosity of the psychiatric risk gene Cacna1c

Abstract: Genetic variation in CACNA1C, which encodes the alpha-1 subunit of CaV1.2 L-type voltage-gated calcium channels, is strongly linked to risk for psychiatric disorders including schizophrenia and bipolar disorder. To translate genetics to neurobiological mechanisms and rational therapeutic targets, we investigated the impact of mutations of one copy of Cacna1c on rat cognitive, synaptic and circuit phenotypes implicated by patient studies. We show that rats hemizygous for Cacna1c harbour marked impairments in le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…We have demonstrated in this study that the compensatory mechanisms affecting neuronal excitability can be ameliorated pharmacologically with the administration of selective agonists such as 77-LH-28-1 rescuing impairments in synaptic integration and plasticity, a proof of principle that may be applicable to other psychiatric disorder risk variants. For example, an increase in input resistance due to the administration of 77-LH-28-1 could facilitate spike backpropagation, potentially rescuing the plasticity impairment reported in the Cacna1c+/model of genetic vulnerability to schizophrenia (76). Highly selective muscarinic M1 receptor agonists have efficacy clinically with negligible side effects(77-80) making them attractive pharmaceutical tools.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated in this study that the compensatory mechanisms affecting neuronal excitability can be ameliorated pharmacologically with the administration of selective agonists such as 77-LH-28-1 rescuing impairments in synaptic integration and plasticity, a proof of principle that may be applicable to other psychiatric disorder risk variants. For example, an increase in input resistance due to the administration of 77-LH-28-1 could facilitate spike backpropagation, potentially rescuing the plasticity impairment reported in the Cacna1c+/model of genetic vulnerability to schizophrenia (76). Highly selective muscarinic M1 receptor agonists have efficacy clinically with negligible side effects(77-80) making them attractive pharmaceutical tools.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit discordant results sometimes, there are lower levels of BDNF in both medicated and nonmedicated SCZ patients when compared to controls (Favalli et al, 2012). Previous studies have found deficits in the levels of Bdnf in mice harbouring forebrain-specific conditional knockout of Cacna1c (Lee et al, 2016), the prefrontal cortex of both CaV1.2 haploinsufficient rats ( ) and persons with CACNA1C risk-associated genetic variants upon analysis of the BRAINEAC data (Sykes et al, 2019;Tigaret et al, 2021). Indeed, BDNF is associated with synaptic transmission and neural plasticity (Carvalho et al, 2008;55 Gottmann, Mittmann and Lessmann, 2009;Favalli et al, 2012).…”
Section: Molecular Pathway Analysis Of Cacna1c Mutantsmentioning
confidence: 97%
“…In addition, missense mutations in exons 8 or 8a of CACNA1C cause a rare subtype of ASD called Timothy syndrome 1 via a gain-of-function (GOF) mechanism [9,18]. Thus, there is a large interest in characterising the consequences of CACNA1C aberrations, as recently illustrated [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the functional roles of CaV1.2 in psychiatric disorders have been obtained from genetic rodent models [9,19] and to a lesser extent using zebrafish genetic models [22,23]. Except for a recent aforementioned study [23], the role of cacna1c within the context of normal brain function, behaviour, and disease in zebrafish, has been underexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation